Development of Teaching Materials Based on Realistic Mathematics Education to Improve Understanding of Fractions in Fourth-Grade Elementary School Students - Resti, Meri; Sulistiyo, Urip; Haryanto, Eddy (Journal of Innovation and Research in Primary Education, 2025)
Students' understanding of fractions in fourth-grade elementary school remains low due to the lack of contextual and engaging teaching materials. This study aims to develop teaching materials based on Realistic Mathematics Education (RME) to enhance students' understanding of fractions. The research method used is Research and Development (R&D) with the 4D model (Define, Design, Develop, Disseminate), though it was limited to the Develop stage due to time constraints. Expert validation results indicate that the teaching material has a very high level of validity. A limited trial conducted on 10 fourth-grade students showed an improvement in understanding by 45%-54%. Additionally, teacher feedback revealed that this teaching material is highly practical and easy to use in learning. The RME approach, which emphasizes the mathematization of real-world situations, has proven to help students grasp fraction concepts more effectively than conventional methods. Thus, RME-based teaching materials can serve as an innovative alternative to improving the quality of mathematics learning in elementary schools.